IMPLEMENTASI METODE JIBRIL DALAM MENINGKATKAN KUALITAS PEMBELAJARAN AL-QUR'ANMATERI SURAH AL-HUJURAT/49:13 KELAS IV SDNEGERI 2 JEDONG - Bayidi, Ahmad; Gafur, Abd.; Barizi, Ahmad (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
This research is based on the problem. What are the results of learning the Al-Qur'an using the Jibril method and audio-visual media on the material Surah Al-Hujurat/49:13 Class IV SD Negeri 2 Jedong Wagir Academic Year 2023/2024? Meanwhile, the aim of this research is to improve students' ability to read the Al-Qur'an and the quality of Al-Qur'an learning in the Islamic Religious Education learning process on the material "Let's Recite and Study the Q.S. Al-Hujurat/49:13 and Hadith about Diversity” after using Jibril's method and audio visual media for class IV SD Negeri 2 Jedong Wagir for the 2023/2024 academic year. This research uses three rounds of action research. Each round consists of four stages, namely: Planning, Action, observation and reflection. The target of this research is class IV students for the 2023-2024 academic year. Based on research, it has been proven that there has been an increase in Islamic Religious Education learning outcomes for class IV students at SD Negeri 2 Jedong in 2023/2024 who have reached the KKM, before implementing learning using the Jibril method, Islamic Religious Education learning outcomes for class IV students were still low. After implementing learning using the Jibril method in the first cycle, namely with a total of 30 students. 18 students have completed with a percentage of 60%, while 12 students have not completed with a percentage of 40%. Furthermore, in the second cycle, 24 students completed it with a percentage of 80%, while 6 students did not complete it with a percentage of 20%. It can be concluded that the application of learning using the singing method can improve the learning outcomes of class IV students at SD Negeri 2 Jedong in 2023/2024, namely from the number of students who completed 18 students (60%) in cycle I and 24 (80%) students in cycle II. This means that there has been a very significant increase, reaching 20%